2010
DOI: 10.1182/blood-2009-11-255109
|View full text |Cite
|
Sign up to set email alerts
|

In search of the original leukemic clone in chronic myeloid leukemia patients in complete molecular remission after stem cell transplantation or imatinib

Abstract: It is not clear if absence of BCR-ABLtranscripts-complete molecular response (CMR)-is synonymous with, or required for, cure of chronic myeloid leukemia (CML). Some patients achieve CMR with imatinib (IM), but most relapse shortly after treatment discontinuation. Furthermore, most patients in long-term remission (LTR) post-stem cell transplantation (SCT) are considered functionally cured, although some remain occasionally positive for low-level BCR-ABL mRNA. Interpretation of the latter is complicated because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 35 publications
2
47
0
Order By: Relevance
“…19 The methodological approach was very similar to our own, except that nesting was not used. Nesting was found not to confer higher sensitivity than an efficient and specific real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…19 The methodological approach was very similar to our own, except that nesting was not used. Nesting was found not to confer higher sensitivity than an efficient and specific real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is the measurement of BCR-ABL fusion junctions from genomic DNA, an approach that is technically demanding and labor intensive because the genomic breakpoints need to be characterized for each patient and individual detection assays designed and validated. 20,30,31 Notwithstanding these technical hurdles, one study reported that all patients (n ¼ 10) who lost CMR after imatinib cessation had detectable levels of BCR-ABL on analysis of genomic DNA, and patients who maintained CMR displayed a stable level of BCR-ABL DNA. 20 These data may provide a rationale to use genomic DNA as a methodology to monitor residual disease, at least on a research basis.…”
Section: Towards the Path To A Curementioning
confidence: 99%
“…This has led us and others to investigate the use of patient-specific BCR-ABL genomic DNA breakpoints as an investigational test to improve the lower limit of detection of MRD. [17][18][19][20] In order to perform patient-specific DNA PCR in CML, it is necessary to identify the BCR-ABL fusion region and to design primers for each patient to ensure specificity for the unique fusion sequence (Figure 1). The use of a patient-specific DNA sequence as the marker of the leukaemic clone is well established in acute lymphoblastic leukaemia, in which the target sequence is either the immunoglobulin gene or the T cell receptor gene rearrangement.…”
Section: Measuring the Level Of Mrdmentioning
confidence: 99%